2014
DOI: 10.1039/c4fd00040d
|View full text |Cite
|
Sign up to set email alerts
|

Boron doped diamond biotechnology: from sensors to neurointerfaces

Abstract: Boron doped nanocrystalline diamond is known as a remarkable material for the fabrication of sensors, taking advantage of its biocompatibility, electrochemical properties, and stability. Sensors can be fabricated to directly probe physiological species from biofluids (e.g. blood or urine), as will be presented. In collaboration with electrophysiologists and biologists, the technology was adapted to enable structured diamond devices such as microelectrode arrays (MEAs), i.e. common electrophysiology tools, to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For a more detailed description see Hébert et al 5 Three different heights of CNTs (1 mm, 2 mm, and 3 mm) were coated with 25 nm boron-doped diamond. As control, at nanocrystalline diamond (NCD) structures as described by Hébert et al 20 were used. One sample of the DCNTs (1 mm) and one control sample can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For a more detailed description see Hébert et al 5 Three different heights of CNTs (1 mm, 2 mm, and 3 mm) were coated with 25 nm boron-doped diamond. As control, at nanocrystalline diamond (NCD) structures as described by Hébert et al 20 were used. One sample of the DCNTs (1 mm) and one control sample can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Rigid diamond microelectrode arrays showed the properties of the diamond combined to that of microelectrodes. They were first used for electrochemical sensing [146][147][148][149][150][151] and were more recently suggested and tested for neural interfacing [152][153][154][155][156][157]. Moreover, despite the high growth temperature of diamond some teams managed to transfer BNCD electrodes on polymer substrates in order to create flexible devices [158,159].…”
Section: Diamond Devicesmentioning
confidence: 99%
“…Hence to meet this demand 3D diamond wells where developed [156]. The 3-D fabrication process is very challenging especially during the photolithography steps because of the high topography due to the surface mould.…”
Section: D Flexible Diamond Electrodesmentioning
confidence: 99%
“…In this perspective, the field of boride clusters essentially is very rich. As doping of the bulk metal clusters with boron diversifies the physical and electronic properties, this can be utilized as common strategy for studying both the electronics as well as surface chemistries of the metal borides [19][20][21][22][23][24][25][26][27][28][29]. Several reviews and articles have demonstrated that the area of metal-rich metallaboranes as well as boron-rich metallaboranes are expanding briskly .…”
Section: Introductionmentioning
confidence: 99%